2019
DOI: 10.3892/etm.2019.7452
|View full text |Cite
|
Sign up to set email alerts
|

The combination of catechin, baicalin and β‑caryophyllene potentially suppresses the production of inflammatory cytokines in mouse macrophages in vitro

Abstract: It has been demonstrated that the combination of three botanical factors of (+)-catechin, baicalin and β-caryophyllene, which exhibit anti-inflammatory effects, with comparatively lower concentrations of each factor, demonstrating a potent synergistic-suppressive effect on the growth of mouse macrophage RAW264.7 cells in vitro, and suggesting it may function as a pharmacologic tool for managing inflammatory diseases. The present study was undertaken to determine the suppressive effects of (+)-catechin, baicali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The anti-inflammatory activity of açaí is often associated with the presence of flavonoids, such as catechin and epicatechin, both in the pulp fruit [ 18 ] and in the seeds [ 19 ]. Catechin’s anti-inflammatory effect is well described alone, acting via the regulation of Toll-like receptor (TLR) 2/4 and inflammasome signaling [ 20 ], or in combination with other compounds, suppressing the production of inflammatory cytokines in mouse macrophages in vitro in association with baicalin and β-caryophyllene [ 21 ], and inhibiting the activation of TLR4-MyD88-mediated nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen activated protein kinase (MAPK) signaling pathways in RAW 264.7 macrophages in association with quercetin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of açaí is often associated with the presence of flavonoids, such as catechin and epicatechin, both in the pulp fruit [ 18 ] and in the seeds [ 19 ]. Catechin’s anti-inflammatory effect is well described alone, acting via the regulation of Toll-like receptor (TLR) 2/4 and inflammasome signaling [ 20 ], or in combination with other compounds, suppressing the production of inflammatory cytokines in mouse macrophages in vitro in association with baicalin and β-caryophyllene [ 21 ], and inhibiting the activation of TLR4-MyD88-mediated nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen activated protein kinase (MAPK) signaling pathways in RAW 264.7 macrophages in association with quercetin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, β-caryophyllene improved the reduction of the macrophage number induced by metaxalone [30]. Similarly, Yamaguchi et al [31] have found that a short 5 h exposure to a low concentration (5 µM) of β-caryophyllene counteracted the LPS-induced release of pro-inflammatory cytokines without affecting the basal levels of IL-1 β, IL-6, and TNF-α, but lowered them after LPS stimulation. Similarly, a 48 h exposure to α-humulene, at concentrations of 755 and 1555 µM, inhibited the inflammatory response induced by LPS, by lowering the release of nitric oxide (NO), in murine macrophages RAW 264.7 [32].…”
Section: Ability Of Caryophyllane Sesquiterpenes To Modulate Macropha...mentioning
confidence: 70%
“…Curcumin and Resveratrol (RSV) have been deeply described for their anti-inflammatory property both in monocytic and endothelial cells (Rana et al 2016 ; Schwager et al 2017 ; Sun et al 2015 ), whereas BCP was only recently identified as an anti-inflammatory compound (Yamaguchi and Levy 2019 ). However, to the best of our knowledge, this is the first study evaluating the effect in vitro of bCUR, RSV and, BCP combined together (data are summarized in Table 1 ), as described in the novel dietary supplement Fenoxidol™.…”
Section: Discussionmentioning
confidence: 99%